Histopathology laboratory paperwork as a potential risk of COVID-19 transmission among laboratory personnel - Abdulkarim Hasan; Khalid Nafie; Osama Abbadi (Elsevier, 2020)
SUMMARY: Background: Healthcare workers have a higher risk of acquiring coronavirus disease 2019 (COVID-19). The process of requesting pathological investigations is usually handled manually through paper-based forms. This study evaluated the potential for paper-based request forms to transmit severe acute respiratory virus coronavirus-2 (SARS-CoV-2) to laboratory staff in order to make recommendations for dealing with hospital paperwork in a post-COVID-19 world. Methods: Paper-based forms were tracked from the time of test ordering until the release of the pathology report by calculating the time taken for the forms to reach the laboratory, and the exposure of each staff group to forms received from both high and moderate COVID-19 risk areas. Results: Four hundred and thirty-two (83%) of 520 forms were received in the laboratory within 24 h. The remaining 88 (17%) forms took ≥24 h to be handled by laboratory personnel. The mean daily exposure time to the paperwork for various laboratory staff was as follows: receptionists, 2.7 min; technicians, 5.5 min; and pathologists, 54.6 min. Conclusion: More than 80% of the forms were handled by laboratory personnel within 24 h, carrying a high potential risk for viral transmission. It is recommended that paper-based request forms should be replaced by electronic requests that could be printed in the laboratory if required. Another option would be to sterilize received paperwork to ensure the safety of laboratory personnel. More studies are needed to detect the stability of SARS-CoV-2 on different surfaces and determine the potential risk of COVID-19 transmission via paper.